2020
DOI: 10.1007/s10049-020-00713-8
|View full text |Cite
|
Sign up to set email alerts
|

„Leben retten bis der Arzt kommt?“

Abstract: Zusammenfassung Hintergrund Einsätze in Notfallsituationen bei Patienten mit fortgeschrittener, unheilbarer Erkrankung stellen für das Rettungsdienstpersonal eine besondere Belastung dar. Für ersteintreffendes nichtärztliches Rettungsdienstpersonal ergeben sich dabei Situationen, in denen Entscheidungen getroffen werden müssen, die außerhalb des erlernten oder rechtlich zugesicherten Kompetenzbereichs liegen. Ziel dieser Arbeit war daher die Darstellung von Konflikten und deren … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is therefore not surprising that our study also showed that decisions were regularly made against one's own ethical values, in order to protect oneself against the threat of legal action (by relatives or colleagues) [3,18]. This was also perceived as demanding by about half of the respondent rescue service personnel [7].…”
Section: Comparison Of Criteria-driven Decisions Of Emergency Physici...mentioning
confidence: 80%
See 2 more Smart Citations
“…It is therefore not surprising that our study also showed that decisions were regularly made against one's own ethical values, in order to protect oneself against the threat of legal action (by relatives or colleagues) [3,18]. This was also perceived as demanding by about half of the respondent rescue service personnel [7].…”
Section: Comparison Of Criteria-driven Decisions Of Emergency Physici...mentioning
confidence: 80%
“…Based on the distress analysis of the interviewed rescue personnel, which was published elsewhere, it was shown that especially patientrelated and structural con ict dimensions were perceived as burdensome and occurring regularly, which underlines the corresponding wishes and ideas of the rescue personnel [7].…”
Section: Analysis Of the Transfer Of (Legal) Competenciesmentioning
confidence: 85%
See 1 more Smart Citation